2011
DOI: 10.1002/pola.25010
|View full text |Cite
|
Sign up to set email alerts
|

End‐group fidelity of copper(0)‐meditated radical polymerization at high monomer conversion: an ESI‐MS investigation

Abstract: Copper(0)-mediated radical polymerization (single electron transfer-living radical polymerization) is an efficient polymerization technique that allows control over the polymerization of acrylates, vinyl chloride and other monomers, yielding bromide terminated polymer. In this contribution, we investigate the evolution of the end-group fidelity at very high conversion both in the presence and in the absence of initially added copper (II) bromide (CuBr 2 ). High resolution electrospray-ionization mass spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 81 publications
4
92
1
Order By: Relevance
“…48 Extending further it has been shown that in general, copper(0) mediated polymerization has excellent end group fidelity in comparison to other atom transfer processes. [49][50][51][52] Again, the current model would predict that under conditions of fast deactivation, such is the case in these polymerizations, termination and transfer events, which are typically long time scale, should be reduced with respect to propagation, thus allowing for the ultra high molecular weight polymers with near to 0 mol% termination that have been seen already. Although for acrylates this may be explained simply by the large k p /k t ratio, for vinyl chloride it has been shown that the molecular weight can exceed that of free radical polymerization 45 which can only be the case when molecular weight limiting reactions such as chain transfer to monomer and termination are reduced in comparison to propagation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Extending further it has been shown that in general, copper(0) mediated polymerization has excellent end group fidelity in comparison to other atom transfer processes. [49][50][51][52] Again, the current model would predict that under conditions of fast deactivation, such is the case in these polymerizations, termination and transfer events, which are typically long time scale, should be reduced with respect to propagation, thus allowing for the ultra high molecular weight polymers with near to 0 mol% termination that have been seen already. Although for acrylates this may be explained simply by the large k p /k t ratio, for vinyl chloride it has been shown that the molecular weight can exceed that of free radical polymerization 45 which can only be the case when molecular weight limiting reactions such as chain transfer to monomer and termination are reduced in comparison to propagation.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2). 49,52,59 Ultrahigh M w polymers possible with copper(0) mediated radical polymerizations/SETDTLRP 45,50 Low termination rates due to (i) low copper concentrations 60 and (ii) low termination rate coefficients relative to propagation of monomers employed 61,62 High deactivation rate suppresses termination and chain transfer processes…”
Section: Resultsmentioning
confidence: 99%
“…27,28 For example, SET-LRP is effective for a large panel of monomers such as acrylates, 27,29,30 methacrylates, [31][32][33][34] acrylamides, 35 acrylonitrile, 36 and vinyl chloride. 37,38 This polymerization technique allows high halogen functionality at the chain end, 39 even at high monomer conversion, and is compatible with numerous polar solvents such as dimethyl sulfoxide (DMSO), 26,40 water, 41 alcohols, 42,43 beers, 44 acetic acid, 45 and nonpolar solvent/additives mixtures. 46 More remarkably, Percec and coworkers 47 have demonstrated the controlled polymerization of methyl acrylate (MA) by SET-LRP in the presence of various amount of 4-methoxyphenol, which is a frequently used stabilizer.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,26,37,38,47 It is important to mention that from many LRP methods that provide polymers with narrow molecular weight distribution, only SET-LRP generates polymers with both narrow molecular weight distribution and quantitative or near quantitative chain-end functionality. 6,7,[48][49][50][51]57,[71][72][73][74][75][76][77] Narrow molecular weight distribution is an important feature of the polymers prepared by LRP but the most significant structural parameter of these polymers is the quantitative or near quantitative chain-end functionality combined with narrow molecular weight distribution. Chain-end functionality is the major parameter of a polymer that allows the construction of complex architectures such as multiple block copolymers, 64,73,[76][77][78][79] and dendrimers by iterative synthesis.…”
Section: Introductionmentioning
confidence: 99%